Magnetic anisotropies effect on the Spin-Seebeck response in spinel ferrite thin films (2022)
ABSTRACT: Observation of spin Seebeck effect (SSE) at room temperature in a weak ferromagnetic material, for example, a spinel zinc ferrite (ZnFe2O4) in bulk and thin film is demonstrated. In order to understand the physics behind this effect, a systematic structural and magnetic characterization with the SSE signal in this ferrite is presented. Measurements of Surface analysis by x-ray hotoemission (XPS) and absorption (XAS) spectroscopies, and x-ray magnetic circular dichroism (XMCD) provide information about the cationic distribution in the lattice, which is found to be responsible of the magnetic response in the material. The magnetic anisotropy, as well as the Gilbert constant of the ferrite have been investigated by means of ferromagnetic resonance measurements. These measurements are useful to predict the spin Seebeck response in the material.